Social Dimension in the Hadiths of Ihsan - Candra, Onrico; Fata, Azamel; Zulfikri, Zulfikri; Anshari, Fauzan; M, Buchari; Zain, Irfan (Nida Al-Qur'an: Jurnal Pengkajian Islam, 2024)
This study aims to examine the social dimension in the hadiths of the Prophet SAW containing the word ihsan contained in the kutul al-tis'ah (nine popular hadith books) with initial information from Mausu'ah Nadhratun Na'im. Through a qualitative approach, this study analyzes the texts of the hadiths of the Prophet SAW containing the word ihsan to identify the social dimension, it is expected that readers can deeply understand the relevance of ihsan in the modern social context and its important role in building an ethical and prosperous society. The results of the analysis show that through the hadiths of ihsan, the Prophet SAW emphasized the importance of doing good and giving the best in every aspect of life. Ihsan not only includes spiritual awareness that Allah always watches over every deed and focuses on the goodness of the individual, but also emphasizes good actions towards others, starting from the smallest community, namely family, relatives, neighbors, to the wider community. By practicing the values ??of ihsan, individuals can contribute to the creation of a harmonious and mutually supportive social environment.